Fostering Cross-Cultural Understanding among Indonesian EFL Students: Exploring Progress and Challenges - Musaldin, La Ode (Al-TA'DIB: Jurnal Kajian Ilmu Kependidikan, 2025)
This narrative literature review explores the progress and challenges of promoting cross-cultural understanding (CCU) among Indonesian students through English as a Foreign Language (EFL) instruction. In response to the increasing demands of globalization and Indonesia’s rich multicultural landscape, the government has incorporated CCU into the national curriculum, notably the Kurikulum Merdeka. The review highlights the integration of local cultural elements in textbooks and classroom practices and emphasizes EFL teachers’ pivotal roles in fostering intercultural awareness. However, the study reveals persistent obstacles, including overemphasis on local cultures, skepticism toward foreign cultural content, and teachers’ static views of culture. These factors hinder students’ global cultural competence. The review concludes with implications for policymakers, educators, and researchers, advocating for balanced cultural exposure and professional development.